Iron Man 3 - Feige, Kevin; Pearce, Drew, 1975-; Black, Shane; Downey, Robert, Jr., 1965-; Paltrow, Gwyneth, 1972-; Cheadle, Don; Pearce, Guy, 1967-; Hall, Rebecca, 1982-; Szostak, Stephanie; Dale, James Badge, 1978-; Favreau, Jon; Kingsley, Ben, 1943-; et al. (Burbank, Calif. : Buena Vista Home Entertainment, 2013)
When Tony Stark (aka Iron Man) finds his entire world reduced to rubble, he must use all his ingenuity to survive, destroy his enemy, and somehow protect those he loves. But a soul-searching question haunts him, does the man make the suit, or does the suit make the man?
Title from container
Originally released as a motion picture in 2013
Blu-ray Disc special features: Marvel one-shot : Agent Carter (short film); Iron Man 3 unmasked (featurette); Deconstructing the scene : attack on Air Force One (featurette); Behind-the-scenes look : Thor, the dark world (featurette); deleted and extended scenes; gag reel; audio commentary by Shane Black and Drew Pearce
DVD special features: Deconstructing the scene : attack on Air Force One (featurette); Behind-the-scenes look : Thor, the dark world (featurette)
Music, Brian Tyler ; editors, Jeffrey Ford, Peter S. Elliot ; director of photography, John Toll
Robert Downey, Jr., Gwyneth Paltrow, Don Cheadle, Guy Pearce, Rebecca Hall, Stephanie Szostak, James Badge Dale, Jon Favreau, Ben Kingsley
Keywords: Iron Man (Fictitious character) -- Drama; Terrorists -- Drama; Superheroes -- Drama; Superhero films; Action and adventure films; Feature films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities